1995
DOI: 10.1080/01904169509365095
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between shoot and root characteristics of white clover cultivars differing in response to phosphorus

Abstract: Root dry weight and the relationship between shoot and root characteristics for 119 white clover (Trifolium repens L.) cultivars and breeding lines were examined at five (40, 120, 200, 400, and 500 mg P/kg soil) phosphorus (P) levels. There were significant (P<0.01) differences among cultivars for root dry weight and root/shoot ratio. Instantaneous root/shoot ratio decreased with increasing P supply up to 200 mg P/kg, and then increased again from 400 to 500 mg P/kg soil. Allometric analysis indicated that roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…But differences due to varieties and variety X nutrient level interaction were significant only in case of P. A negative correlation existed (r = -0.555; n =35) between SDW and RSR in case of P-stressed plants suggesting an increase in RDW production at the cost of SDW. Similar negative correlation between RSR and SDW was also reported by Caradus et al (1995). No such correlation was, however, observed in case of N-stressed plants.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…But differences due to varieties and variety X nutrient level interaction were significant only in case of P. A negative correlation existed (r = -0.555; n =35) between SDW and RSR in case of P-stressed plants suggesting an increase in RDW production at the cost of SDW. Similar negative correlation between RSR and SDW was also reported by Caradus et al (1995). No such correlation was, however, observed in case of N-stressed plants.…”
Section: Resultssupporting
confidence: 72%
“…The work of last two decades has established sufficient evidence to believe that genotypic differences among crop species and varieties (in absorption and utilization of mineral nutrients) can be exploited to improve fertilizer-use efficiency, and to obtain higher productivity on nutrient deficient soils (Saric, 1987;Baligar and Fageria, 1990). Differential responses of different varieties of a crop to N (Sarma and Sarma, 1994;Jorgensen, 1997) and P (Caradus et al, 1995;Yan et al, 1995;Vegh et al, 1997) have been reported, making identification of nutrient efficient crops varieties a useful strategy for improving yields under low input agricultural systems in developing countries like Pakistan. Such exploitation will not only help in classifying the existing genetic material into nutrientefficient or inefficient, responsive or non-responsive but will also provide information/data base for future breeding ventures.…”
Section: Introductionmentioning
confidence: 99%
“…Trifolium repens lack of yield response may be explained by the very small increases in shoot S concentration, even with very large inputs of S fertiliser. This is an unusual result, however, for a legume species considered to be high yielding with moderate to high fertiliser requirements (Caradus et al 1995). It was the only species to behave in this manner.…”
Section: S Responsementioning
confidence: 91%
“…Much research has been conducted into white clover (T. repens L.) dry matter (DM) and growth responses to added P in NZ (Caradus & Snaydon 1986;Caradus et al 1995). As such, highly productive clover species and pastures are generally adapted to highfertility soil conditions and do not perform well in infertile and/or acid soil conditions (Haynes & Williams 1993;Moir et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Diversion of growth from shoot to root (higher RSR) is considered as a possible mechanism for plant adaptability under nutrient stress through efficient exploitation of culture medium (Fö hse, Claassen, and Jungk 1991). Some workers have suggested that an increase in RSR of the plants under nutrient stress is at the cost of SDM (Fredeen, Rao, and Terry 1989;Caradus, Makey, and Bosch 1995). This is generally attributed to the greater export of photosynthates from shoots to roots, mainly due to repressed sink activity in shoots (i.e., reduced leaf expansion and shoot growth rate).…”
Section: Discussionmentioning
confidence: 98%